2019
DOI: 10.1186/s41938-019-0184-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of some commercial formulations of entomopathogenic fungi on the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae)

Abstract: The tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a major threat to tomato production in Rwanda. Laboratory bioassays were conducted to evaluate some commercial entomopathogenic fungi (EPF) formulations on T. absoluta larvae. The larvae, inside the leaf galleries, were obtained from the established tomato field. Commercial EPF: Metatech® WP [Metarhizium anisopliae (Metschn.) Sorok, Strain FCM Ar 23B3], Beauvitech® WP [Beauveria bassiana (Bals.) Vuill., Strain J25], and Botanigard ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
1
27
1
1
Order By: Relevance
“…In the current study, it was revealed that there was no immediate effect (within three days of application) of B. bassiana on T. absoluta larvae, as the establishment of the fungi took a few days. This was in agreement with another study, which demonstrated that the fungal infection was very low in the first 3 days, and started to be significantly different among the treatments from the fourth day, after the application in Rwanda [56]. Similarly, Shiberu and Getu (2018) [40] also recorded that the mortality rate increased up to 78%, after 10 days of treatment in different locations of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, it was revealed that there was no immediate effect (within three days of application) of B. bassiana on T. absoluta larvae, as the establishment of the fungi took a few days. This was in agreement with another study, which demonstrated that the fungal infection was very low in the first 3 days, and started to be significantly different among the treatments from the fourth day, after the application in Rwanda [56]. Similarly, Shiberu and Getu (2018) [40] also recorded that the mortality rate increased up to 78%, after 10 days of treatment in different locations of Ethiopia.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Klieber and Reineke (2016) [55] also reported high mortality rates and significant reductions in larval longevity, when the larvae were fed for a period of around 15 days, on leaves with B. bassiana propagules. At the dosage of 10 8 spores/mL, the highest mortality rate was recorded [56], and the mortality rate of T. absoluta and different concentrations of B. bassiana had a linear relationship [54]. It was generally observed that the mortality rates increased with an increase in time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high sporulation potential of EPF over the cadavers enhanced horizontal pest infection through the self-spore contamination process [ 64 ]. Besides, our isolates scored shortest (1.93 to 3.17 days) median lethal time (LT 50 ) at 10 8 spores·ml -1 , which were different from the two commercially formulated Beauveria (Beauvitech® WP and Botanigard® ES) that scored somewhat extended LT 50 values of 5.2 and 6.6 days at the same spore concentration against T. absoluta , respectively [ 62 ]. This is at least twice the LT 50 value of the Ethiopian isolates presented here.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, recently explored Ethiopian isolate of B. bassiana displayed 95.8% of mortality against third instar larvae of T. absoluta at 2.5 × 10 9 spores·ml -1 [ 61 ]. In all cases, Ethiopian isolates of B. bassiana performed better than the commercially formulated products (Beauvitech® WP) that scored 60.8% of larval mortality against T. absoluta at 10 8 spores·ml -1 in Rwanda [ 62 ]. This could infer that locally screened isolates might be pathogenically effective than commercialized ones, and geographic origin of isolates may determine their pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of treated M. anisopliae and B. bassiana isolates at 10 8 spore ml −1 concentration against T. absoluta larvae, LT 50 values were determined as 3.9 and 5.2 days and 82.8 and 60.8% mortality rates (Ndereyimana et al 2019). The application of the same isolates at a concentration of 2.5 × 10 9 conidia ml −1 recorded a mortality rate of 87.50% for M. anisopliae and 95.83% for B. bassiana.…”
Section: Resultsmentioning
confidence: 99%